Janus formosus - Basov, S. A. (Zenodo, 2024)
Janus formosus (Zhelochovtsev, 1935) Figs 1A–K Cephus formosus Zhelochovtsev, 1935, March: 150; Taeger et al ., 2010: 49. Janus orientalis Gussakovskij, 1935, October: 83; Zhelochovtsev, 1968: 49 (as synonym of J. formosus ); Taeger et al ., 2010: 49. TYPE MATERIAL EXAMINED. Holotype of Cephus formosus Zhelochovtsev, 1935: “Ussuri, Olga distr, Shkotovo, 6. V.1927, A. Zhelochovtsev”; “ Cephus formosus nov. sp. ♀ Typus A. Zhelochovtsev det. 1930”; golden circle. [ZMMU]. Holotype of Janus orientalis Gussakovskij, 1935: “der. Khungara, 280 v. vniz po Amuru ot Khabarovska, 15. VI.[1]911, Soldatov”; “ Janus orientalis typus V. Gussakovskij”; “ Holotype Janus orientalis Gussakovskij 1935 vide A. Taeger 2014, red label” “DEI-GISHym 30271”; golden circle [ZISP]. ADDITIONAL MATERIAL EXAMINED. Russia : Primorsky Territory: Vladivostok, Sedanka, 1–14. VI 1979, 4♂, 9♀ (A. Zinovjev) [ZISP]; same locality, 3. VI 1978, 1♀ (A. Lelej) [IBSS]; 20 km SE of Ussuriysk, GTS, 30. V 1990), 1♀ (S. Belokobylskij [ZISP]; 30 SE of Ussuriisk, Kamenushka, 7. VI 1979, 1♀ (A. Zinovjev) [ZISP]; Station Gvozdevo, 10 km E of Posjet, 30. V 1979, 1♀ (A. Zinovjev) [ZISP]; Chyornye Mountains, Luna Mt., Kraskino, 6. VI 1962, 1♀ (O. Kovalyov) [ZISP]; Barabash-Levada, 18. VI 1980, 1♀ (S. Konovalov) [ZISP]; Lyalichi, Ilistaya River, 3. VI 1990, 1♀ (S. Belokobylskij) [ZISP]. Khabarovsk Territory: 24 km S of Khabarovsk, 29. V 1983, 2♂ (A. Zinovjev) [ZISP]; Khehtsyr, 4. VI 1983, 5♂, 1♀ (D. Kasparyan) [ZISP]; Khehtsyr, 18-st km, 8. VI 1983, 1♂ (D. Kasparyan) [ZISP]; Slavianka, Khehtsyr, 17-th km, 3.VII 1983, 2♂ (D. Kasparyan) [ZISP]; Khehtsyr, Vysokogornyi, 9–10.VII 1983, 2♀ (D. Kasparyan) [ZISP]; 20 km NE of Troitskoe, 23. VI 1983, 1♀ (D. Kasparyan) [ZISP]. Sakhalin Province, Kuriles, SW Kunashir I., Krivonozhka Spring, 20–22. VI 2013, 1♂, 3♀ (Yu. and L. Sundukov) [ZISP]. REDESCRIPTION. Female (holotype). Measurements. Total body length: 9.2 mm; fore wing: 7.5 mm. Colour . Body black; mandibular yellow with orange tips of tooth and black stripe basally; ...